Comparison of a new multiplex immunoassay for measurement of ferritin, soluble transferrin receptor, retinol-binding protein, c-reactive protein and α1-acid-glycoprotein concentrations against a widely-used s-ELISA method - Karakochuk, Crystal; Henderson, Amanda; Samson, Kaitlyn; Aljaadi, Abeer; Devlin, Angela; Becquey, Elodie; Wirth, James; Rohner, Fabian (MDPI, 2018)
Recently, a multiplex ELISA (Quansys Biosciences) was developed that measures ferritin, soluble transferrin receptor (sTfR), retinol-binding protein (RBP), C-reactive protein (CRP), α1-acid glycoprotein (AGP), thyroglobulin, and histidine-rich protein 2. Our primary aim was to conduct a method-comparison study to compare five biomarkers (ferritin, sTfR, RBP, CRP, and AGP) measured with the Quansys assay and a widely-used s-ELISA (VitMin Lab, Willstaett, Germany) with use of serum samples from 180 women and children from Burkina Faso, Cambodia, and Malaysia. Bias and concordance were used to describe the agreement in values measured by the two methods. We observed poor overall agreement between the methods, both with regard to biomarker concentrations and deficiency prevalence estimates. Several measurements were outside of the limit of detection with use of the Quansys ELISA (total n = 42 for ferritin, n = 2 for sTfR, n = 0 for AGP, n = 5 for CRP, n = 22 for RBP), limiting our ability to interpret assay findings. Although the Quansys ELISA has great potential to simplify laboratory analysis of key nutritional and inflammation biomarkers, there are some weaknesses in the procedures. Overall, we found poor comparability of results between methods. Besides addressing procedural issues, additional validation of the Quansys against a gold standard method is warranted for future research